KEMAMPUAN SISWA DALAM MEMAHAMI TEKS BAHASA INGGRIS PADA SISWA SEMESTER KEDUA DI SMAN 1 BENAI - Yeni, Fitri; Azhar, Fadly; ', M. Nababan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research was designed to describe the students’ ability incomprehending English texts. The aim was to find out students ability in comprehendingthe text. This descriptive research took place in SMAN 1 Benai in March 2016. Thesample was 40 students from XI IPA3 class that took by using cluster random sampling.In collecting the data, there were 30 questions that included in this test. The durationtime for doing the test was 90 minutes. The data was analyzed by calculating thestudents’ score individually and finding out the mean score. The students’ scoreclassified into five level mastery; they are: very poor, poor mediocre, good, andexcellent. The data was presented by using graphic. Based on the result finding of thisresearch, the students’ ability in comprehending English texts at second year of SMAN1 Benai was in good level. Meanwhile, the mean score of the whole students’ scores was62.2.Keywords: Students’ Ability, Comprehending English Texts